The Impact of Using Electronic Banking Services in Achieving Financial and Inclusion and Sustainable Development (The International Journal for Scientific Research, 2024)
The study aimed to investigate the impact of using mobile banking services through mobile phones on achieving financial inclusion and its implications for sustainable development. The descriptive analytical approach was employed and a questionnaire was used as a data collection tool from 439)) users of mobile banking services (Mobile Money) at the Cooperative and Agricultural Credit Bank. The data was statistically analyzed using multiple regression analysis. The results showed the significance of the study's multiple models in representing the relationship between the independent variable (use of mobile banking services), the intermediate variable (financial inclusion) and the dependent variable (sustainable development). The findings revealed that customers' use of mobile banking services has a positive effect on achieving financial inclusion and positively reflects on sustainable development as well. The study's model explained about 65% of the variance in sustainable development goals. It was found that there is a significant positive relationship between all the variables.To assess the strength of relationships in the assumed model, a statistical analysis of the Survey data was done according to the structural equation model (SEM) using the Analysis Moment of Structures program (AMOS) supported by the Statistical Package for the Social Sciences program (SPSS).The study recommended enhancing cooperation between banks and relevant entities to expand financial inclusion and achieve sustainable development.In conclusion, the study provided empirical evidence on the role of mobile banking in promoting financial inclusion and its contributions towards realizing sustainable development targets.
Keywords: Electronic Banking Services via Mobile Phone; Financial Inclusion; Sustainable Development